Supramolecular helices from helical building blocks via head-to-tail intermolecular interactions. Issue 94 (16th November 2021) - Yan, Xiaosheng; Weng, Peimin; Shi, Di; Jiang, Yun-Bao
Abstract : Helical building blocks can self-assemble into supramolecular helices  via  head-to-tail intermolecular interactions, wherein good propagation of helicity operates, exhibiting favourable homochiral elongation and functional helical channel structures. Abstract : Supramolecular helices from helical building blocks represent an emerging analogue of the α-helix. In cases where the helicity of the helical building block is well propagated, the head-to-tail intermolecular interactions that lead to the helix could be enhanced to promote the formation and the stability of the supramolecular helix, wherein homochiral elongation dominates and functional helical channel structures could also be generated. This feature article outlines the supramolecular helices built from helical building blocks, i.e., helical aromatic foldamers and helical short peptides that are held together by intermolecular π–π stacking, hydrogen/halogen/chalcogen bonding, metal coordination, dynamic covalent bonding and solvophobic interactions, with emphasis on the influence of efficient propagation of helicity during assembly, favouring homochirality and channel functions.